The first molecular survey of theileriosis in Malaysian cattle, sheep and goats - Kho, K.L.; Amarajothi, A.D.G.; Koh, F.X.; Panchadchram, C.; Nizam, Q.N.H.; Tay, S.T. (Elsevier, 2017)
This study reports the molecular detection of Theileria spp. from six cattle farms, a sheep farm and a goat farm located at different states in Peninsular Malaysia. Animal b lood samples were screened for the presence of Theileria DNA using a conventional polymerase chain reaction (PCR) assay. A total of 155 (69.2%) of 224 cattle investigated were PCR-positive for Theileria DNA. The occurrences of Theileria spp. ranged from 17.5% to 100.0% across six cattle farms. Theileria DNA was detected from 90.0% of 40 sheep but none of 40 goats examined in this study. Sequence analyses of amplified 18S rRNA partial fragments (335-338 bp) confirmed the identification of Theileria buffeli, Theileria sergenti, and Theileria sinensis in representative samples of cattle and ticks. T. luwenshuni was identified in the infected sheep. The high occurrences of Theileria spp. in our farm animals highlight the needs for appropriate control and preventive measures for theileriosis.